The Influence Of Financial Distress, Operational Complexity, Audit Opinion, And Audit Tenure On Audit Delay - Sianipar, Maria; Sudarma, Made (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This study aims to provide empirical evidence on the factors influencing audit delays in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The independent variables used in this quantitative study are financial distress, operational complexity, audit opinion, and audit tenure. The sample was selected using purposive sampling, with data obtained from publicly accessible financial statements and annual reports. The data were analyzed using multiple linear regression in SPSS version 25. The results indicate that audit opinion has a significant negative effect on audit delay, whereas financial distress, operational complexity, and audit tenure have no significant effect.